Smart System Model to Disinfect SARS-CoV 2 in Physical Environments - Ocaña, Jesús; Flores, Erick; Niquin, Esmelin; Pacheco, Alex; Felix, Edwin (The journal of contemporary issues in business and government, 2021)
The present research project is the development of a de-disinfectant robot model (intelligent system), capable of moving and recognizing the physical environment to disinfect it from SARS-CoV2, by means of Ultraviolet C and Ozone light, having double disinfection. To this end, certain systematized actions have been carried out, such as achieving the training of artificial neural networks (ANN), multilayer perceptron using Matlab software, later programming logic in Arduino IDE, and then the implantation of the code in the Arduino microcontroller. The simulations of the disinfecting robot processes have allowed observing the behavior of its movement, location, obstacle detection, activation of the disinfectant module, timing of stages and disinfection of the environment. All this has been carried out and achieved within the Concurrent Design methodological framework that contains five stages: conceptual design, kinematic analysis, dynamic analysis, mechanical design and simulation. As a concrete result, there is the design of the disinfecting robot with a height of 1.35 meters, and that in its structure it has sensors, actuators and peripherals. In addition, estimates of time, distance, travel, motor rotation and displacement of the ANN disinfectant robot have been obtained using mathematical models, such as odontometric equations, state space system and fundamentally neural networks.